2019
DOI: 10.1007/s40279-019-01236-0
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Effective Training Dose Required to Increase 1RM Strength in Resistance-Trained Men: A Systematic Review and Meta-Analysis

Abstract: The aim of this multi-experiment paper was to explore the concept of the minimum effective training dose (METD) required to increase 1-repetition-maximum (1RM) strength in powerlifting (PL) athletes. The METD refers to the least amount of training required to elicit meaningful increases in 1RM strength. A series of 5 studies utilising mixed methods, were conducted using PL athletes & coaches of all levels in an attempt to better understand the METD for 1RM strength. The studies of this multi-experiment paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 54 publications
3
50
0
1
Order By: Relevance
“…Respectively, regular and periodic practice / training of 1RM nullifies or at least reduces the difference in power caused by any power training (heavier or with easy loading) and it indicates that the most part of differences in power is connected with practice of 1PM which improves neuromuscular adaptation (Morton et al, 2016). However meta-analysis of Androulakis-Korakakis P and his colleagues showed that performing one approach of 6-12 repeats with loads in the range of 70-85 % of 1RМ, 2-3 times a week before achieving a will or short-term muscle failure within 8-12 weeks can lead to a significant power increase in bench press and squats in men (Androulakis- Korakakis et al, 2019). Participants of the main group trained at pedaling power of 100 % of MOC, it corresponds to the range of 80-85 % of 1RМ.…”
Section: Resultsmentioning
confidence: 99%
“…Respectively, regular and periodic practice / training of 1RM nullifies or at least reduces the difference in power caused by any power training (heavier or with easy loading) and it indicates that the most part of differences in power is connected with practice of 1PM which improves neuromuscular adaptation (Morton et al, 2016). However meta-analysis of Androulakis-Korakakis P and his colleagues showed that performing one approach of 6-12 repeats with loads in the range of 70-85 % of 1RМ, 2-3 times a week before achieving a will or short-term muscle failure within 8-12 weeks can lead to a significant power increase in bench press and squats in men (Androulakis- Korakakis et al, 2019). Participants of the main group trained at pedaling power of 100 % of MOC, it corresponds to the range of 80-85 % of 1RМ.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation factor (f.corr) of 0.80 [32] was used for both the PEIC and sham/control groups. To estimate inter-study heterogeneity the I2 statistic was used, where I2 = 25% was considered low, I2 = 50% moderate and I2 = 75% high [33].…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies have demonstrated that performing resistance training once or twice per week can minimize the loss of cardiorespiratory function [ 36 ] or, more specifically, maintain [ 37 , 38 ] or improve maximum strength [ 39 ] in some populations. Specifically, after an 8-week strength training period Tavares et al [ 38 ] reported that half-squat one-repetition maximum strength and quadriceps cross sectional area were maintained when performing either 1 or 2 training sessions per week over a subsequent 8-week detraining period (exercise regime: 3–4 sets of 6–12 RM half-squat and knee extension exercise) when compared to ceasing training entirely.…”
Section: Training Cessation Effects On Muscle Strength Power and mentioning
confidence: 99%